Scolochloa marchica Düvel, Ristow & H. Scholz – a German-Polish endemic species of the lowlands and the distribution of S. festucacea (Willd.) Lk. in Poland - Kruk, Jerzy; Ristow, Michael; Jedrzejczyk, Iwona (Biodiversity: Research and Conservation, 2024)
In the current study, an extensive worldwide herbarium search, including over 1500 herbarium sheets of Scolochloa festucacea (Willd.) Lk., was performed to find specimens of S. marchica Düvel, Ristow & H. Scholz. The latter is a recently described new species, whose primary distribution was found to be limited to the Brandenburg region in Germany and the Wolin Island in Poland. As a result of the query, S. marchica was not identified in any regions other than those previously known. This indicates that it is a German-Polish endemic species, with a limited distribution range. Taking advantage of flow cytometry, we analysed for the first time the nuclear DNA content of both Scolochloa species and the obtained 2C values correlated exactly with their chromosome numbers. These data allowed us to put forward a hypothesis of evolution of S. marchica from S. festucacea. The new results, together with those previously published, confirmed that we deal with a distinct species. Taking into account recent records of this endemic species, it is currently known from 9 extant and 6 historical localities in Germany. Field search for the species in its only historical locality in Poland, on the Wolin Island, was unsuccessful. The critical revision of herbarium and literature records of S. festucacea from the territory of Poland allowed us to generate an updated distribution map of this declining species, which deserves special protection.